Semi-Global Cooperative Output Regulation Problem for Heterogeneous Swarm Systems With Input Saturation Under Switching Network - Gao, Jialong; Sun, Lei; Xiang, Xiaojia; Song, Hongwei; Long, Yiming (IEEE access, 2019)
In this paper, the semi-global cooperative output regulation problem of heterogeneous swarm systems subject to saturation under switching network is investigated. Like the common consensus problems, the swarm systems consist of some followers cannot access the state of the leader directly. But the difference is that some even cannot measure the state of the leader all the time. By utilizing the distributed output feedback control method, the low-gain feedback technique and the output regulation theories, we establish two sets of consensus control laws, respectively, based on the state feedback method and the output feedback method, to solve the output consensus problems in this kind. Besides, the global leader-following output consensus problem under switching network is proved to be a special case of semi-global cooperative output regulation problem under switching network, and as a consequence, it can also be solved by our method. A simulation example is proposed to illustrate the results very well.